IMPLEMENTASI MANAJEMEN BALANCED SCORECARD DI PONDOK PESANTREN JAM’IYYAH ISLAMIYYAH TANGERANG SELATAN - Saihu Saihu (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
This paper aims to determine the effectiveness in the management of Islamic boarding schools using balanced scorecard performance analysis, including using four perspectives, finance, customers, internal business processes and learning and growth in the Islamic boarding school Jam'iyyah Islamiyyah. This research uses a qualitative approach with a descriptive model. Based on research that has been done, it is known that the management of the Islamic boarding school Jam'iyyah Islamiyyah with a balanced scorecard approach is categorized as good. Because the measurement in four perspectives is close to the expected target. After being measured by the balanced scorecard approach and then analyzed with the effectiveness indicators according to Danim, the results obtained by the management of the Jam'iyyah Islamiyyah Islamic boarding school can be said to be effective.